Effects of intermittent hypoxia training on hematological indices and aerobic performance - Li, X.; Hu, Y.; Li, W.; Tian, Z.; Zhang, L.; Lin, X.; Su, P. (Journal of Exercise Science & Fitness, 2004)
In order to investigate the effects of intermittent hypoxic training on hematological indices and aerobic performance, 28 college students were randomly divided into 4 groups, with 7 in each group: 1) living high-training low group (HiLo); 2) living high control group (HiC); 3) living low-training low group (LoLo); and 4) living low control group (LoC). HiLo and HiC were exposed to hypobaric hypoxia (2,500 m simulated altitude) for 12 hours each day for 4 weeks. HiLo and LoLo performed a training of 3 km submaximal running at sea level on each day while HiC and LoC did not perform any exercises during the training period. The results showed that red blood cell (RBC), hemoglobin (Hb) and hematocrit (Hct) increased from the baseline values with hypoxic exposure and reached to peak levels after 19 days. Mean corpuscular volume was maintained throughout the training period. Subjects' V in HiLo and HiC increased significantly by comparing with that before hypoxia exposure. No change in V02max was found in LoLo and LoC. Moreover, subjects' 3 km performance was also improved significantly after the intermittent hypoxia training period. Such findings suggested that intermittent hypoxia training could increase RBC, Hb, Hct, and 3 km running performance.